2016
DOI: 10.5301/ejo.5000740
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Structural Changes in Systemic Arterial Hypertension: An OCT Study

Abstract: Ganglion cell complex thickness decrease is possibly a better retinal marker for hypertensive changes with respect to RNFL and macular thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
(24 reference statements)
1
16
1
4
Order By: Relevance
“…There have been studies reporting defects in RNFL and GCC in hypertensive patients, [15][16][17] which differ from the findings of our study. Han-Min Lee et al found a significant decrease in RNFL thickness in hypertensive retinopathy patients in a longitudinal study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There have been studies reporting defects in RNFL and GCC in hypertensive patients, [15][16][17] which differ from the findings of our study. Han-Min Lee et al found a significant decrease in RNFL thickness in hypertensive retinopathy patients in a longitudinal study.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have suggested the diagnostic ability of the GCC to detect hypertensive changes in the retina and demonstrated the correlation between inner retinal layer thickness and microvascular metrics. 12,15 We believe that further longitudinal studies are necessary to establish the association between hypertension and structural changes in RNFL and GCC.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,17 In the last decade, OCT studies have also confirmed RNFL thinning as a form of hypertensive retinal damage. 30 Yu et al 31 found a close correlation between RPC volume and RNFL thickness. These reports suggest that retinal vessel rarefaction may be associated with neural damage in patients with essential hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…It can distinguish ten retinal layers with high resolution, and has the advantage of quantitatively evaluating the thickness of each layer. In HTN patients without retinopathy or glaucoma, thinning of the GC-IPL and peripapillary RNFL was reported 3,4,27 . In our study, there was no difference in the CMT, but the GC-IPL and RNFL thicknesses were different among the three groups, and those of HTN group 2 was thinner than the control group.…”
Section: Discussionmentioning
confidence: 99%